2017
DOI: 10.1371/journal.pone.0190143
|View full text |Cite
|
Sign up to set email alerts
|

Temporal trends in educational inequalities in non-communicable diseases in Korea, 2007-2015

Abstract: BackgroundSocioeconomic inequalities in non-communicable diseases are known to exist; however there is a paucity of research describing the secular trends in these inequalities. To this end, the current study aims to explore the recent time trends in social patterning of selected non-communicable diseases among Korean adults between 2007 and 2015.MethodsUsing data from the Korea National Health and Nutrition Examination Survey (KNHANES), temporal trends in socioeconomic inequalities in diabetes, arthritis, ast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 54 publications
4
7
0
Order By: Relevance
“…Even after controlling for baseline SES and health behaviour, Cox proportional hazards model regressions showed that lower educational level was positively associated with the incidences of diabetes and stroke among both men and women, and with hypertension only among women. The observations of the inverse educational gradients were largely consistent with those of preceding studies (for diabetes [2, 1012, 18], stroke [2, 5], and hypertension [2, 13]).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Even after controlling for baseline SES and health behaviour, Cox proportional hazards model regressions showed that lower educational level was positively associated with the incidences of diabetes and stroke among both men and women, and with hypertension only among women. The observations of the inverse educational gradients were largely consistent with those of preceding studies (for diabetes [2, 1012, 18], stroke [2, 5], and hypertension [2, 13]).…”
Section: Discussionsupporting
confidence: 90%
“…Thus, the RII indicates the ratio of the odds of each outcome at the lowest educational level (with the ridit score = 1) to those at the highest level (with the ridit score = 0). The RII has been often used to assess educational inequalities in health outcomes by preceding studies [4, 18, 24, 39].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thirty-four studies (71.0%) employed a compositional approach to measuring SEP. Of those 34 studies, 17 depended on a single parameter and classified SES level according to a continuous or dichotomous distribution or standardized categori-zation. In these studies, the principal indicators were traditional measures of education [12][13][14][15][16][17][18], household income [19][20][21], and occupation [22,23]. Some studies specified the SES level according to proxy measures such as type of health insurance or health-insurance premium levels, which are determined in proportion to one's comprehensive living status [24][25][26][27][28].…”
Section: Compositional Socioeconomic Position Measuresmentioning
confidence: 99%